ASK CULTURAL COMPETENCY SELF-ASSESSMENT SCALE: ADAPTATION TO TURKISH, VALIDITY AND RELIABILITY STUDY - Uzunaslan, Şerif; Çifci, Elif Gökçearslan (Aile ve Sosyal Hizmetler Bakanlığı, 2022)
In this study, the scale named “ASK Cultural Competency Self-Assessment Scale” developed by Leung and Cheung (2013) was adapted to Turkish by obtaining the necessary permissions from the developers of the scale. The working group consists of 245 social workers actively working in the field of social work. The internal consistency coefficient calculated as 0,952 for the whole scale. Cronbach's alpha values calculated as 0,875 for the attitude evaluation dimension, 0,864 for the skill assessment dimension and 0,926 for the knowledge assessment dimension. The differences between the 27% lower and upper groups were examined in order to ensure the reliability procedures. In the analysis it was observed that there were statistically significant differences between the lower and upper groups (t (130):21,93, p

Bu çalışmada, Leung ve Cheung (2013) tarafından geliştirilen “ASK Cultural Competency Self-Assessment Scale” adlı ölçek, ölçeğin geliştiricilerinden gerekli izinler alınarak Türkçeye uyarlanmıştır. Çalışma grubunu sosyal hizmet alanında aktif olarak çalışan 246 sosyal hizmet uzmanı oluşturmaktadır. İç tutarlılık katsayısı (Cronbach’s alpha) ölçek bütünü için 0,952; tutum değerlendirme boyutu için 0,875; beceri değerlendirme boyutu için 0,864 ve bilgi değerlendirme boyutu için 0,926 olarak hesaplanmıştır. Güvenirlik işlemlerini sağlamak amacıyla %27’lik alt ve üst gruplar arasındaki farklar incelenmiştir. Yapılan çözümlemede (t (130):21,93, p
KÜLTÜREL YETKİNLİK KENDİNİ DEĞERLENDİRME ÖLÇEĞİ: TÜRKÇEYE UYARLANMASI, GEÇERLİK VE GÜVENİRLİK ÇALIŞMASI